Processing method of acceleration signal with zero drift. Issue 3 (June 2021) - Shi, Yonglei; Fang, Liqing; Li, Rongxiang; Guo, Deqing; Zhang, Sa; Tang, Qiongjie
Abstract: An economical and effective method to measure displacement is to integrate the acceleration signal. Because of the zero drift in the acceleration sensor, there will be a trend term in the process of acceleration secondary integration, which will cause some errors in displacement measurement. In this paper, several methods of acceleration signal processing with zero drift are given, and the advantages and disadvantages of these methods as well as the applicable occasions are analysed, which have important reference value for selecting reasonable methods in dealing with engineering problems.